Actitudes hacia la conservación del ambiente en pobladores de la comunidad de Manacamiri. Río Nanay. Distrito de Punchana. 2021 - Mozombite Nuñez, Cintia Vanessa (2022)
The work is called: attitudes towards environmental conservation in residents of the Manacamiri community, Nanay River, Punchana District. 2021, the objective was set to evaluate the attitudes towards environmental conservation of the residents of the Manacamiri community, Nanay River. Punchana District. Loreto Region, in the cognitive, affective and reactive dimensions. The research work is descriptive-transversal. Having a simple probabilistic sample of 70 people who live in Manacamiri. The following results are available, regarding the cognitive dimension, the people in the study area reached the good level (75.7%) and 24.3% of the excellent level. For the reactive dimension, the people surveyed reached an excellent (50%) and good (47.1%) level. For the affective components, these people rate excellent (51.4%) and good (47.1%). As a final conclusion, the majority of residents of the community of Manacamiri, Nanay River, have a good attitude, favorable to environmental conservation (65.7%).